2015
DOI: 10.1007/s00455-015-9625-2
|View full text |Cite
|
Sign up to set email alerts
|

Use of Thickened Liquids to Manage Feeding Difficulties in Infants: A Pilot Survey of Practice Patterns in Canadian Pediatric Centers

Abstract: Improved survival rates of sick or preterm infants have resulted in an increase of observed feeding difficulties. One common method for managing feeding difficulties in infants is to manipulate liquid viscosity by adding thickening agents to formula or expressed breast milk. Concerns regarding the lack of clinical practice guidelines for the use of this strategy have been raised in the literature and in clinical settings for several years. This study aimed to survey feeding clinicians working in major Canadian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 32 publications
(42 reference statements)
0
17
0
Order By: Relevance
“…Currently, the provision of thickened liquids is a commonly used intervention to facilitate safe milk ingestion in the presence of thin liquid aspiration. 35,36 This intervention is aimed at slowing the rate of milk flow through the pharynx in effort to promote a timely initiation of swallow and obtain complete airway protection. Although this intervention may have beneficial effects for some, the ability to achieve these effects is limited by the nature and severity of the swallowing impairment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the provision of thickened liquids is a commonly used intervention to facilitate safe milk ingestion in the presence of thin liquid aspiration. 35,36 This intervention is aimed at slowing the rate of milk flow through the pharynx in effort to promote a timely initiation of swallow and obtain complete airway protection. Although this intervention may have beneficial effects for some, the ability to achieve these effects is limited by the nature and severity of the swallowing impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the provision of thickened liquids is a commonly used intervention to facilitate safe milk ingestion in the presence of thin liquid aspiration . This intervention is aimed at slowing the rate of milk flow through the pharynx in effort to promote a timely initiation of swallow and obtain complete airway protection.…”
Section: Discussionmentioning
confidence: 99%
“…For example infant formula needs significantly longer to thicken and results in a higher final viscosity [54*]; concern was a reported of the lack of guidance [55]. Thickening occurs more slowly at refrigerated temperature (5°C) and even more slowly for refrigerated milk, which may require 45-60 minutes [56] and reaches a higher final viscosity, increasing with fat content [57*] and protein content [58].…”
Section: Current Practice and Standardisation Approaches Internationallymentioning
confidence: 99%
“…In powdered IMF, reducing the protein content to as low as 9.77 g protein/100 g did not cause a significant impact on physical stability and shelf-life [26]. However, in RTF liquid IMF, a higher ratio of α-Lac to β-Lg reduces the viscosity and induces rapid sedimentation during storage, as observed in UHT-treated products; and hence, the addition of thickener and stabilizer is suggested to manage the viscosity and sedimentation, respectively [27,28,29]. Furthermore, Crowley et al [27] reported increased α-Lac reduced heat-induced coagulation in a model whey protein-dominant IMF.…”
Section: Introductionmentioning
confidence: 99%